TOOMPEA HILL STABILITY ANALYSIS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1997)
On Toompea Hill situated in the center of Tallinn there are several natural, ancient architectural and historical monuments. It has become apparent that the processes in the rock mass caused an unfavorable environmental side effect accompanied by significant subsidence of the Toompea Hill. Identification of the reasons of the Toompea Hill's subsidence and opening the physical substance of these processes is the main aim of the present work. For the feasibility study stability problems were investigated. Accordingly, it was decided to perform numerical modeling analysis using two-dimensional Fast Lagrangian Analysis of Continua (FLAG - program) (1). It is suitable for stability analysis, for parametric and sensitivity studies. For the first time, preliminary calculations before the modeling have been proposed. This method enabled to simplify and quicken the further modeling. It was made by means of conventional calculation methods, using theoretical formulas. The utility of preliminary calculations was clearlyproved. At first, little field information was available to estimate the rock mass properties. For this estimation, geological data were used. The rock mass properties were selected, based on Bieniawski's rock mass rating (RMR) (2).